Faster Function Blocks for Precision Timed Industrial Automation - Pearce, Hammond; Roop, Partha; Biglari-Abhari, Morteza; Schoeberl, Martin (2018 IEEE 21st International Symposium on Real-Time Distributed Computing (ISORC), 2018)
In industrial automation, safety-critical control systems need robust timing guarantees in addition to functional correctness. Unfortunately, devices that are typically used in this domain, such as Programmable Logic Controllers, often feature architectures that are not amenable to static timing analysis, for instance relying on general purpose microprocessors or embedded operating systems. As a result, designers often rely on timing values gained from simple measurement of running applications, an approach that only provides very weak guarantees at best. The synchronous approach for IEC 61499 Function Blocks, in contrast, has been demonstrated to be time predictable when run on appropriate hardware, such as simple microprocessors. However, simple microprocessors are often not fast or powerful enough for modern automation requirements. In this paper, we examine how the performance of synchronous IEC 61499 can be improved through the usage of the multi-core T-CREST architecture, data scratchpads, and an optimised compiler. Overall, our improvements resulted in 60% shorter worst-case execution times.